Nitrite Reduction Enhancement on Semiconducting Electrode Decorated with Copper(II) Aspirinate Complex - Sayão, Fabiana A. [UNESP]; da Silva Flor, Jader Barbosa [UNESP]; Frem, Regina Célia Galvão [UNESP]; Stulp, Simone; Cardoso, Juliano C. [UNESP]; Zanoni, Maria V. B. [UNESP] (Springer Nature, 2016)
The present work seeks to describe a new approach characterized by copper(II) aspirinate complex deposited onto nanotube TiO2 electrodes as mediator of electron transfer during nitrite reduction, aiming at achieving a faster removal of nitrite to nitrogen species oxides. Thin films of copper aspirinate ([Cu2(asp)4]) on the Ti/TiO2 nanotube surface are easily obtained following multi-scans (100 cycles) recorded for the Ti/TiO2 electrode in 0.1 mol L−1 NaCl, pH 4, containing 5.0 × 10−4 mol L−1 of the copper coordination compound. The complex showed high adherence while the cyclic voltammograms presented redox peaks at −0.15/+0.15 V, which was attributed to the reduction of Cu(II) to Cu(I). Following 5 min of treatment using photoelectrocatalysis on Ti/TiO2-[(Cu)2Asp4] electrode, a total removal of nitrite was observed, which was found to be at least four times faster compared to Ti/TiO2 electrode. Concomitantly, we also observed a relatively good conversion to nitrogen-containing gaseous species (56 %) besides the formation of 42 % of ammonia. The results, in effect, also indicate that nitrate and nitrite are not detectable in the treated solution up to levels of 0.5 mg L−1. The method under consideration has successfully accounted for the maximum limit of nitrite recommended in drinking water which has been set to 1 mg L−1. [Figure not available: see fulltext.]
Keywords: Copper(II) aspirinate complex; Nitrite removal; Photoelectrocatalysis reductive process; Photoelectrocatalytic reduction of nitrite